The social context of technological experiences - Kamath, Anant, author.
1 online resource (x, 148 pages)
Keywords: This book demonstrates how technology and society shape one another and that there are intrinsic connections between technological experiences and social relationships. It employs an array of theoretical concepts and methodological tools to examine the technology-society nexus among three urban groups in India (traditional caste-based handloom weavers, subaltern Dalit communities, and informal female labour). It provides evidence of how innovations such as industrial technologies, communication technologies, and workplace technologies are not only about strides in science and engineering but also about politics and sociology on the ground. The book contributes to the growing research in innovation studies and technology policy that establishes how technological processes and outcomes are contingent on complex sociological variables and contexts. The author offers an inclusive, holistic, and interdisciplinary approach to understanding the field of innovation and technological change and development by involving various methodologies (network analysis, archival work, oral histories, focus group discussions, interviews). The book will serve as reference for researchers and scholars in social sciences, especially those interested in development studies, science and technology policy and innovation studies, information and communication technology (ICT) policy, public policy, management, social work and research methods, economics, sociology, social exclusion and subaltern studies, women's studies, and South Asian studies. It will also be useful to nongovernmental organisations, activists, and policymakers.